Perancangan Ulang Interior Pusat Kebugaran Fit For Two Fitness Center Kota Bogor Dengan Pendekatan Well-being Design - Izza Khairullah, Muhammad; Adli Wismoyo, Erlana; Primiana Yuniati, Arnanti (Telkom University, 2024)
The shift in modern lifestyles has led to an increased demand for fitness facilities that accommodate a variety of exercise trends. The Fit for Two Fitness Center in Bukit Cimanggu City, Bogor, requires redesigning to meet these needs. This redesign aims to support the community's fitness activities by creating open, warm, and welcoming spaces that align with the residential culture. A